Addressing Overlapping Migratory Categories within New Patterns of Mobility in Peru - Blouin, Cécile; Button, Emily (Anti-Trafficking Review, 2018)
This article reflects on the construction and application of different migratory categories in the Peruvian context, including irregular migrants, refugees, victims of trafficking, and smuggled migrants. Through legal analysis and interviews with key migration actors in the country, the paper explores the ways in which Peru responds to migrants in these different categories, in view of the recent changes in human mobility in the country. The article aims to shed light on the fragmentation of migratory categories and the negative effects this has on migrants’ human rights. It is exploratory in nature and serves as a starting point for further debate on the subject.